AN ANALYSIS OF TEACHERS’ STRATEGIES IN TEACHING ENGLISH AT SMP NEGERI 2 TONDANO - Kusman, Gritty A. M; Oroh, Elisabeth Z.; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research was conducted to analyze what strategies teachers use in teaching English and what factors influence these strategies. This research is descriptive qualitative research on English teachers at SMP Negeri 2 Tondano. Data collection was carried out through interviews with English teachers at the school. Data analysis was carried out using methods of recognition and organization, coding and interpretation and representation. Based on research findings, there are four teaching strategies used by teachers and three factors that influence them. These strategies are discussion strategies, presentation strategies, using lecture/explanation methods as learning media, using image media and providing reinforcement at the end of the teaching and learning process. There are three factors that influence the strategies of English teachers at SMP 2 Tondano. The first is the student factor which includes the background of the major taken by the student, as well as the condition of the student in participating in the learning process. The second is a factor that comes from the teacher. This factor concerns the teacher's ability to utilize technology to support teaching strategies. Lastly, facilities include how limited learning facilities are.